Gambaran Penggunaan Obat Tradisional untuk Pengobatan Mandiri Masyarakat Desa Badang RW 03 Kecamatan Ngoro Kabupaten Jombang - Machfiroh Setianing Hati; Reni Ariastuti; Risma Sakti Pambudi (Yayasan Literasi Sains Indonesia, 2023)
Self-medication is an individual's effort to recognize symptoms or diseases and can choose drugs to cure that. The use of traditional medicine has been used by the community in curing minor ailments. This study was conducted in order to see an overview of the use of traditional medicine for self-medication in the Badang Village area, RW 03. This research is a descriptive and qualitative non-experimental research that has been tested for content validity. Sampling was done by purposive random sampling with inclusion criteria, namely age 17-60 years old, had experienced self-medication using traditional medicine. The results showed that the traditional medicines used by the Badang community for self-medication were Jamu, OHT, and Fitofarmaka. In addition, there are ways to use traditional medicines that can be drunk directly and processed first, such as boiled, grated, and brewed. Then the types of diseases that can be treated using traditional medicine to treat minor ailments such as colds, fever, coughs and colds, and diarrhea.